3(x+2)=6(x-1)+6

Simple and best practice solution for 3(x+2)=6(x-1)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)=6(x-1)+6 equation:


Simplifying
3(x + 2) = 6(x + -1) + 6

Reorder the terms:
3(2 + x) = 6(x + -1) + 6
(2 * 3 + x * 3) = 6(x + -1) + 6
(6 + 3x) = 6(x + -1) + 6

Reorder the terms:
6 + 3x = 6(-1 + x) + 6
6 + 3x = (-1 * 6 + x * 6) + 6
6 + 3x = (-6 + 6x) + 6

Reorder the terms:
6 + 3x = -6 + 6 + 6x

Combine like terms: -6 + 6 = 0
6 + 3x = 0 + 6x
6 + 3x = 6x

Solving
6 + 3x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
6 + 3x + -6x = 6x + -6x

Combine like terms: 3x + -6x = -3x
6 + -3x = 6x + -6x

Combine like terms: 6x + -6x = 0
6 + -3x = 0

Add '-6' to each side of the equation.
6 + -6 + -3x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -3x = 0 + -6
-3x = 0 + -6

Combine like terms: 0 + -6 = -6
-3x = -6

Divide each side by '-3'.
x = 2

Simplifying
x = 2

See similar equations:

| -16=y-13 | | 60-.04x=80 | | 3/10-(-2/3) | | -3=z-18 | | 30+3*x-2*(12-x)=38 | | 10-2m=m+4 | | 8y-7=14y+23 | | 4x+12=38 | | -6x^2=-35 | | 10/62 | | 9x-7=6x+38 | | 50=x-15 | | 27x+901= | | 8x-3=5x-57 | | n/4-5=17 | | 5(x+6)-(x+28)=-2x | | f(x)=x-9/X^2-16 | | 8x+2=6x+36 | | 8(3x-4)=14x-2 | | 17x-9x=24 | | 5x-(2x+9)=9 | | -97x+42x= | | 6(7x-6)=27 | | 15-6x=-51 | | c+1.7=2.6 | | 96-3x=8 | | -6i+4= | | 6x-17=-107 | | 5(x-6)-(x+28)=-2x | | (x-3+5i)(x-3-5i)=0 | | 420=(2x+5)x | | 3(5-2m)=27 |

Equations solver categories